Knowledge and behavior of vulva hygiene correlation on the incident of flour albus (whirt) in ma attarbiyah lauwa 2023 - Tahier, Dwi Ghita; Yuliandini, Astri; Syamsiah, Syamsiah (CV. Paperhome Indonesia, 2024)
ABSTRACT Vaginal discharge is one of the reproductive health problems experienced by women throughout the world. The occurrence of vaginal discharge is caused by various factors, one of which is a lack of knowledge and behavioral patterns regarding personal hygiene. 61% of vaginal discharge cases were experienced by women aged 14-21 years and 39% of those aged 23-45 years. Objective: This study aims to determine the influence of vulva hygiene knowledge and behavior on the incidence of flour albus at MA Attarbiyah Lauwa in 2023. Research method: Quantitative type of research with an Analytic Correlational research design with a cross sectional method. This research was conducted at MA Attarbiyah Lauwa in 2023 using a total sampling technique with 49 people as the population. Data collection was carried out by filling out questionnaires directly by female students who were respondents. Data collection was carried out by the researcher himself, when filling out the questionnaire by the female students, he was guided directly by providing an explanation of each questionnaire question by the researcher, so that it was hoped that more objective answers would be obtained which would then be processed and analyzed using chi-square. Research Results: There is a relationship between knowledge and the incidence of vaginal discharge (p value = 0.001), there is a relationship between Vulva Hygiene Behavior and the incidence of vaginal discharge (p value = 0.002). The conclusion of this research is that knowledge and behavior of vulva hygiene are related to the incidence of vaginal discharge at MA Attarbiyah Lauwa in 2023.